(untitled) (Scientia Agropecuaria, 2025)
This review is scientific research that seeks to explore the relationship between the consumption of certain foods and the emotional state, determining the effects that these foods produce when consumed by individuals. The intake of specific foods containing certain functional properties may help enhance our emotional health. There are particular nutrients present in certain foods that play an important role in overall health, especially in brain function. The objective of this review study was to highlight double-blind studies in humans that demonstrate the effectiveness of nutrients present in foods that interact with neurotransmitters (melatonin, endorphins, serotonin, dopamine, and oxytocin), which affect people’s mood and well-being. For this study, specialized journals and scientific articles published in the last five years were selected. The results show that there is a wide variety of foods that contribute to people’s well-being when consumed, and that this is not exclusive to a particular group of foods. Thus, meat products, dairy products, fruits, vegetables, and seafood, among others, contain nutrients with functional properties associated with people’s emotional state. Finally, future studies should incorporate other variables such as ethnic groups, race, age, and body type, which may affect the results obtained.